Penerapan Sanksi Pidana terhadap Anak Sebagai Pelaku Tindak Pidana Penganiayaan di Kabupaten Belu - Vinsensius Naiaki; Orpa Ganefo Manuain; Heryanto Amalo (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Children are the nation's assets as the successors of the nation's founders to make the country a developed country. As the nation's successors, children must receive comprehensive and massive protection. In the Child Protection Law, it is stated that children need special protection in various situations. For children who are in conflict with the law, the State provides legitimacy in the hope of changing children's behavior and the involvement of many parties in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System or later known as the SPPA Law. The case taken by the author is a case where it is explained that a child in conflict with the law is a recidivist or has committed a repeat crime. Child recidivism is basically the same as recidivism in general, the difference is that the perpetrator here is a child. Repetition of criminal acts here means criminal acts committed by children, whether similar or dissimilar criminal acts, including criminal acts completed through diversion. It is explained that the case written is a case of repetition of criminal acts or recidivism committed by children of criminals. The legal process for the criminal act of abuse committed by Rui Vicente alias Aroni's child no longer takes the diversion route because the perpetrator's child is a recidivist. In this regard, child perpetrators are being processed in court by holding trials which are charged under Article 351 paragraph (1) of the Indonesian Criminal Code. UU no. 11 of 2012 concerning the Juvenile Criminal Justice System.